Urgency of Regulating Victims’ Economic Rights in Fictitious Credit Cases Based on Misuse of Personal Data - Hanif Fonda; Faisal Santiago (Journal of Multidisciplinary Sustainability Asean, 2024)
Background. The rapid development of information technology has led to an increase in fictitious credit cases involving the misuse of personal data. Victims often experience significant economic losses, including damaged credit reputation and financial hardship. While Indonesia has implemented the Personal Data Protection Law and the Witness and Victim Protection Law, these regulations lack specific provisions for addressing economic losses caused by such crimes. Purpose. This study aims to explore the urgency of regulating victims’ economic rights in fictitious credit cases involving personal data misuse. It also seeks to identify the gaps in existing legal frameworks and propose new measures to address these issues effectively. Method. The study employs a qualitative approach by analyzing existing laws, regulations, and case studies related to personal data misuse in Indonesia. It highlights the inadequacy of current policies and emphasizes the necessity for legal reform. Results. The findings reveal a significant legal vacuum in protecting victims’ economic rights, including compensation, restitution, and credit reputation restoration. The study underscores the need for comprehensive regulations to ensure justice and economic recovery for victims, as well as improved oversight of personal data management and law enforcement. Conclusion. To protect victims’ economic rights, Indonesia must develop specific regulations addressing fictitious credit cases. Enhancing legal frameworks and strengthening enforcement mechanisms are essential to mitigate the impact of personal data misuse in banking transactions.